2017
DOI: 10.1101/136531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic modeling quantifies the influence of tumor growth kinetics on the response to anti-angiogenic treatment

Abstract: Tumors exploit angiogenesis, the formation of new blood vessels from pre-existing vasculature, in order to obtain nutrients required for continued growth and proliferation. Targeting factors that regulate angiogenesis, including the potent promoter vascular endothelial growth factor (VEGF), is therefore an attractive strategy for inhibiting tumor growth. Computational modeling can be used to identify tumor-specific properties that influence the response to anti-angiogenic strategies. Here, we build on our prev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Building upon the basic growth models (i.e. adapted Gompertz model on tumor phases) and vascular endothelial growth factor (VEGF), the work in [11] trained and validated a model using published in vivo measurements of xenograft tumor volume. The model employed Nonlinear Least Squares (NLS) optimization together with a global sensitivity analysis to determine which of the four tumor growth kinetic parameters impacts the predicted tumor volume most significantly.…”
Section: Predictive Models Of Tumor Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Building upon the basic growth models (i.e. adapted Gompertz model on tumor phases) and vascular endothelial growth factor (VEGF), the work in [11] trained and validated a model using published in vivo measurements of xenograft tumor volume. The model employed Nonlinear Least Squares (NLS) optimization together with a global sensitivity analysis to determine which of the four tumor growth kinetic parameters impacts the predicted tumor volume most significantly.…”
Section: Predictive Models Of Tumor Growthmentioning
confidence: 99%
“…breast versus lung cancer, [5] and each type of treatment (i.e. administered drug) modifies the growth curve [11]. is heterogeneous and sometimes expensive to obtain (e.g.volume assessed from bio-markers, fMRI [1], fluorescence imaging [20], flow cytometry, or calipers [6]).…”
Section: Peculiarities Of Tumor Growth Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, tumor growth data is small, only a few data points with, typically, days level granularity [10] and irregular spacing among measurements [9]. Moreover, the data has high variability due to: within tumor types specifics, therapy effect on tumor growth [11], and heterogeneous measurement types (e.g. bio-markers, fMRI, fluorescence imaging [12], flow cytometry, or calipers [13]).…”
Section: Model Equationmentioning
confidence: 99%
“…3. Phophatase inhibition ("Ptase"): Studies have shown [31,32] that inhibiting MAPK phosphatase (MKP) activity can promote apoptosis signaling. We simulated this effect by decreasing the association rate (K on_dephos ) of the phosphatase with phosphorylated p38MAPK (pp38) and the dephosphorylation rate (K dephos ) by 10-fold.…”
Section: Definition Of Apoptotic Cells Cleaved Poly(adp-ribose) Polymentioning
confidence: 99%